Foetal cerebral blood redistribution in idiopathic polyhydramnios and the impact on perinatal outcomes - Inshirah Sgayer; Yousef Haddad; Yara Nakhleh Francis; Ruba Tuma; Lior Lowenstein; Marwan Odeh (Journal of Obstetrics and Gynaecology)
Background Idiopathic polyhydramnios is associated with adverse neonatal outcome. The aim of this study was to examine the value of the middle cerebral artery pulsatility index (MCA-PI) in predicting adverse perinatal outcome in pregnancies affected by idiopathic polyhydramnios.Methods A retrospective study was performed during 2013–2022 at a tertiary-care university affiliated hospital. The study included singleton pregnancies with idiopathic polyhydramnios. Obstetrical and perinatal outcomes were compared between women with MCA-PI <10th percentile and women with MCA-P ≥ 10th percentile. A composite adverse perinatal outcome was defined as an Apgar score <7 at 5 minutes, umbilical artery pH <7.15, emergent caesarean delivery (CD) or operative delivery due to foetal distress, neonatal intensive care admission or foetal death.Results Among 45,459 pregnancies, 128 (0.3%) had idiopathic polyhydramnios; 27 exhibited MCA-PI <10th percentile. Among the latter, compared to pregnancies with MCA-PI ≥10th percentile group, the rates were higher of emergent CD (25.9% vs. 7.9%, p = 0.017) and adverse perinatal outcomes (37.0% vs. 15.8%, p = 0.020). These differences persisted in a subgroup analysis of women with moderate or severe polyhydramnios. In the MCA-PI <10th percentile group, the median MCA-PI and cerebroplacental ratio were lower: 0.9 vs. 1.7, p < 0.001 and 0.7 vs. 2.1, p < 0.001, respectively. Receiver operating characteristic curve analysis indicated a significant association of MCA-PI with emergent CD/operative delivery for foetal distress (area under curve = 0.672, p = 0.031); the sensitivity was 46.7% and specificity 82.3%. Cerebroplacental ratio values were not associated with adverse perinatal outcomes.Conclusions Idiopathic polyhydramnios might be associated with foetal cerebral blood flow redistribution, potentially contributing to an increased risk of adverse neonatal outcomes. Prospective studies are required to establish the role of foetal Doppler studies in the antenatal surveillance of idiopathic polyhydramnios, and to determine whether evidence of abnormal MCA-PI serves as a reliable predictor of perinatal outcomes, potentially necessitating labour induction.